Conceptualizing Medical Humanities Programs in Low-Resource Settings in Africa. (August 2019) - Eichbaum, Quentin; Reid, Steve; Coly, Ayo; Naidu, Thirusha; Omaswa, Francis
Abstract : The role of the humanities in medical education remains a topic of dynamic debate in medical schools of high-income countries. However, in most low- and middle-income countries, the medical humanities are less topical and rarely even have a place in the curriculum. Reasons for this dearth include inadequate resources to support such programs coupled with misapprehension of the role and significance of the humanities in medical education. In this article, the authors argue that the humanities have a vital role to play in the low-resource settings of African medical education. They discuss the complexities of the continent's sociohistorical legacies, in particular the impact of colonization, to provide contexts for conceptualizing humanities programs in African schools. They outline the challenges to developing and implementing such programs in the continent's underresourced medical schools and present these as four specific conundrums to be addressed. As a general guide, the authors then suggest four nonprescriptive content domains that African medical schools might consider in establishing medical humanities programs. The goal is to jump-start a crucial and timely discussion that will open the way for the feasible implementation of contextually congruent humanities programs in the continent's medical schools, leading to the enhanced education, training, and professional development of its graduating physicians.